2004
DOI: 10.1115/1.1691434
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a Surface Bump or Groove on the Lubricating Performance and Dimple Phenomena in Simple Sliding Point EHL Contacts

Abstract: The influence of a transversely or longitudinally oriented surface bump or groove on the lubricating performance and dimple phenomena in the simple sliding point contact composed of a steel ball and a glass disk has been investigated theoretically with numerical solution of the thermal elastohydrodynamic lubrication (EHL) and experimentally with optical interferometry technique. Good agreement has been obtained between the theoretical and experimental results. It has also been discovered that the surface bump … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 38 publications
0
15
0
1
Order By: Relevance
“…However, the amount of the side leakage decreases with reducing the size (width and depth of micro-groove) and increasing the overall film thickness. Yang et al 32 proved numerically the results of Kaneta. Nakano et al 33 stated that groove patterns have higher fiction coefficients than the flat surfaces because groove patterns have not enough ability to keep the hydrodynamic pressure.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…However, the amount of the side leakage decreases with reducing the size (width and depth of micro-groove) and increasing the overall film thickness. Yang et al 32 proved numerically the results of Kaneta. Nakano et al 33 stated that groove patterns have higher fiction coefficients than the flat surfaces because groove patterns have not enough ability to keep the hydrodynamic pressure.…”
Section: Introductionmentioning
confidence: 91%
“…They attributed that effect to the channeling of the lubricant away from the contact. Although the negative effects observed numerically and experimentally with micro-grooves in the literature, 13,[30][31][32][33] the authors introduce in this paper an innovative approach to obtain benefits from transverse shallow micro-grooves in EHL contacts. The approach depends on eliminating the side leakage along grooves by reducing the length of groove to be less than the diameter of the Hertzian contact.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last 3 decades, the fundamental understanding of the effects generated by such sub-contact scale features on the behaviour of elasto-hydrodynamically lubricated (EHL) contacts have become a research subject of major importance, commonly named -EHL. Unprecedented improvements both in computational techniques [1], and in film thickness measurement methods, allowed important numerical and experimental contributions [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. In the case of hydrodynamic and mixed lubrication, it has been demonstrated that micro-texturing one of the contacting surfaces with optimized micro-dimples could reduce friction and wear [18,19].…”
Section: Introductionmentioning
confidence: 98%
“…Reported benefits of texture can be very substantial: decrease in operating temperature by tens of degrees [5], decrease in friction by 30% [1], moving the Stribeck curve to the left [4], increase in seizure or breakdown load by 2-10 times [5,6], etc. However, in other cases only negative effects have been reported [7,8].…”
Section: Introductionmentioning
confidence: 99%